Exploring 129Xe NMR parameters for structural investigation of biomolecules: relativistic, solvent, and thermal effects - Gonçalves, Mateus A; Andolpho, Gustavo A; da Cunha, Elaine F F; Ramalho, Teodorico C (Journal of molecular modeling, 2022)
In recent years, the study of new probes has aroused great interest in the scientific community around the world. Therefore, in the present work, we present a potential candidate for a new spectroscopic probe, the Xe(CO)3(NNO) conjugated to 2-(4'-aminophenyl) benzothiazole complex, XeABT. For this proposal, chemical shift calculations at the DFT level were performed; thus, a factorial design was carried out in order to choose the best computational method. The best combination was the base function ZORA-def2-TZVP, with the functional PBE0 and considering the relativistic effects with the ZORA implementation. Our findings reveal that the 129Xe chemical shifts are affected by thermal and solvent effects, and considering an enzymatic environment, a significant decrease in δ(129Xe) values is observed, suggesting with the XeABT complex it may be a promising spectroscopic probe.
Keywords: NMR; Xenon Isotopes; thiazoly; Thiazoles; Relativistic effects; Magnetic Resonance Spectroscopy; Solvents; 129Xe; magnetická rezonanční spektroskopie; Probes; Biological systems; izotopy xenonu; rozpouštědla